Hubungan Antara Faktor Usia Dengan Kejadian Kanker Kolorektal Di Rsud Moewardi Surakarta Tahun 2010-2013 - Izzaty, Abdaul Hamas, dr. Utama, Sp. B, dr. Budi Hernawan (2015)
Background: In Indonesia, colorectal cancer is the third most cancer. In 2008, Indonesia ranks fourth in ASEAN for indicent of colorectal cancer. The incidence rate of colorectal cancer is 15 times higher to people with age 50 years old or older than those who are younger around 20-49 years old but in Indonesia, more than 30% cases found on 40 years old or younger. Objective: In order to examine the relation between ages with incident of colorectal cancer in RSUD Moewardi Surakarta year 2010-2013. Metode: This research uses observational analytic method with cross sectional method. In order to test valuable relation between those two variables, it uses Chi- Square test. Result: There are 86 respondents diagnosed with colorectal cancer and non- cancer, divided to two groups of age, which are 20-49 years old and 50-79 years old. Fifty two respondents diagnosed with colorectal cancer, consist of 30 male patients (57,7%) and 12 female patients (42,3%). In range of 20-49 years old, there are 19 patients (36,5%) diagnosed with colorectal cancer whilst in range of 50-79 years old there are 33 patients (63,5%) whom diagnosed with colorectal cancer. Afterwards, the data is analyzed using Chi Square test. The result is p = 0,002 which means there is a realtion between those two variables.